(untitled) (Journal of Medical & Health Sciences Review, 2025)
The FDOFs have become one of the potential alternative drug delivery systems as it has been shown to increase the rate of dissolution, productivity of bioavailability and has also provided better convenience to patients particularly those with swallowing challenges. This paper set out to design, optimize and characterize the rapid-dissolving oral films with a model drug using the solvent-casting method. The different formulations were made through varying the polymer concentration, plasticizer content and superdisintegrant ratio to identify their effect on physicochemical and mechanical characteristics. It was tested on the basis of thickness, surface pH, endurance of folding, weight change, drug contents, disintegration time, tensile strength, and in-vitro drug release. Findings established that all formulations possessed acceptable physical and mechanical properties and the optimized film had uniform thickness (0.095 mm), acceptable tensile strength (16.2 N/mm2), excellent elongation (29%) and perfect surface pH (6.6). Optimized formulation had a rapid disintegration period of 15 seconds which guaranteed rapid dispersion in the oral cavity. In-vitro dissolution tests showed that there was greatly improved drug release by the optimized film with 94 and 99 percent release after 5 and 10 minutes respectively with the pure drug releasing very slowly. The results are a good foundation to prove that FDOFs can significantly enhance drug dissolution and potentially bioavailability. All in all, the research proves that fast-dissolving oral movies are an effective, patient-friendly, and efficient dosage to help the drug achieve a rapid onset of action. It is also suggested that the performance of the newly developed device should be assessed under in-vivo conditions and that stability issues should be tested in the long run.